PERLINDUNGAN FOLKLORE: APAKAH REZIM HAK CIPTA MEMADAI? - Sardjono, Agus (Indonesian Journal of International Law, 2021)
The government of Indonesia has given a protection for folklore in article 10 Undang-Undang Hak Cipta No. 19 Tahun 2002. It means the protection for forlklore is placed under Intellectual Property’s Regime. The protection is about the regulations of permission for using Indonesian folklore by foreigner but there are some problems occurs. Is it right or wrong to place folklore, there are no evidences to prove that a folklore belongs to, do not mind when the folklore is used by foreigner. This article is trying to give a possibility to solve those problems by seeing the folklore protection in China.